Studi Perbandingan Pengungkapan Strategic Focus and Future Orientation antara Indonesia dan Afrika Selatan - Laila Nazma Arifa; Ika Permatasari (CV. ITTC INDONESIA, 2026)
Issues related to global climate change, social and environmental concerns, corporate governance, and the demands of modern investors are driving a shift toward reporting that presents both financial and non-financial information in a single, integrated report. The Integrated Report (IR) serves as a response to the limitations of traditional reporting. This study conceptually examines the principles of strategic focus and future orientation in IR, while also analyzing differences in understanding and application in the implementation of IR in two countries: Indonesia and South Africa. This study employs a qualitative approach using a conceptual-comparative research model to analyze the integrated reports of two telecommunications companies: XL Axiata Tbk and Vodacom Group Ltd. The results indicate that Vodacom Group Ltd discloses strategic information that is more structured, measurable, and integrated with the six capitals, value creation, risks and opportunities, and long-term targets. XL Axiata Tbk's disclosures remain descriptive due to regulatory differences.